Experimentações da fotografia contemporânea nas redes da criação de Rodrigo Braga, Nino Cais e Berna Reale - Reichhardt, Ricardo (2016)
The objective of this dissertation is a reflection about the moment of contemporary experimentation which artists make use of language interaction and the critic about its comunicative aspects, and the formation of the individual, through the process of creation. We utilize the theorical reference of creation in process on the net, of semiotic basis (Peirce), developed by Cecília Salles; and the evolutive process of image production, developed by Lúcia Santaella. With the presentation of many expanded language theories, the reader is presented to the knowledge of the contemporary experimentation, the main pont of this work with which afterwards we can think about the context where each artist is and analise them. Subsequently we present and reflect about three brazilian artists that are in this “contemporary field”: Rodrigo Braga, Nino Cais and Berna Reale. The information explored is composed by a few works of them, photography and videography, analised by the technic point of view – or know-how – and the subjective quality of character – how its constitute. The artists that we have chosen develop very interesting works, each of them articulating information by themselves, serching for the real meaning of art: creation freedom to re-invent, innovate and to experiment different languages